Dihexyl sulfosuccinate biodegradation by mixed cultures - Chmelárová, Z; Závadská, I; Húska, J; Tóth, D (Folia microbiologica, 2000)
The primary biodegradation of dihexyl sulfosuccinate has been demonstrated using two single cultures and three mixed bacterial cultures of Comamonas terrigena. Primary biodegradation was found in all variants. The highest biotransformation rate and efficiency was observed in one of the single strains. No synergistic effect on degradation was found in mixed cultures.
Keywords: kinetika; Biodegradation, Environmental; biodegradace; Comamonas; Culture Media; Surface-Active Agents; povrchově aktivní látky; Water Pollutants, Chemical; Succinates; sukcináty; chemické látky znečišťující vodu; Kinetics; kultivační média